Sistem Pembelajaran Al-Qawa’id Al-Sharfiyah Di Indonesia Dalam Perspektif Neurolinguistik - Danial Hilmi (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2018)
Learning for al-Qawa'id al-Sharfia need a good system to success the proficiency of the Arabic language. Among the rote system of learning is in the form of the concept that developed over the times. One system that is built in modern times, namely the development of the formula set forth in the table that can be used as an alternative in developing learning for al-qawa'id al-Sharfia. Technology is also a concentration of the learners to shorten the time and thought in the absorption media-based learning. Learning for al-Qawaid al-Sharfia in Indonesia in view of the lack of effective implementation of neurolinguistic looked at where the lack of a language environment is optimal. Meanwhile, boarding is able to play its role with the imposition of a higher education in terms of time and opportunity long enough. It is important to leverage the use of the two sides of the brain as well. Therefore, full attention will deliver learners achieve the desired objectives in studying it.